2020
DOI: 10.1371/journal.pone.0244930
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of papillary thyroid microcarcinoma that predispose patients to local recurrence

Abstract: Background Currently, less aggressive treatment or even active surveillance of papillary thyroid microcarcinoma (PTMC) is widely accepted and recommended as a therapeutic management option. However, there are some concerns about these approaches. We investigated whether there are any demographic, clinical and ultrasound characteristics of PTMC patients that are easy to obtain and clinically available before surgery to help clinicians make proper therapeutic decisions. Methods We performed a retrospective cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Furthermore, the rate of LNM varies in frequency from one study to another, ranging between 14% to 40% [ 21 , 22 , 23 ]. Chow et al [ 24 ] and others [ 25 , 26 ] have also documented the negative impact of LNM on recurrence of PTMC patients. However, at present, there are limited studies on the risk factors for LNM in PTMC in Middle Eastern populations.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the rate of LNM varies in frequency from one study to another, ranging between 14% to 40% [ 21 , 22 , 23 ]. Chow et al [ 24 ] and others [ 25 , 26 ] have also documented the negative impact of LNM on recurrence of PTMC patients. However, at present, there are limited studies on the risk factors for LNM in PTMC in Middle Eastern populations.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, of the patients with tumor size larger than 5 mm, the rate of capsular invasion was 23% significantly higher than that of patients with tumor size of 5 mm and below ( P = 0.001). A currently retrospective chart review of 182 PTMC patients found that minimal extrathyroidal extension (ETE) rate was as high as 37.9% (69/182) ( 51 ). Some other researchers have divided PTMCs into two separate groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study of Choi et al ( 16 ) put forward a point of view that, due to clinically apparent lymph node metastasis, AS rarely leads to favorable oncological outcomes. It is highly likely that lymph node metastasis will eventually lead to local recurrence and secondary operations, which greatly increase the risk of hypoparathyroidism and RLN injury during surgery and reduce the quality of life of the patient ( 17 , 18 ). Therefore, it is necessary to precisely stratify patients with PTMC and evaluate the risk of CLNM in these patients; hence, several researchers have attempted to develop optimal predictive models.…”
Section: Discussionmentioning
confidence: 99%